EVALUATION OF THE ANTICYTOTOXIC ACTIVITY OF FICUS GLOMERATA ROXB.LEAF EXTRACT AGAINST DMBA INDUCED MAMMARY CARCINOMA IN RATS - V.DHANA RANGESH KUMAR; G.JEYANTHI; K.GURUSAMY (International Journal of Pharma and Bio Sciences, 2013)
The aim of the present study is to evaluate the in vivo anticancer activity of ethanolic extract of Ficus glomerata on DMBA induced mammary carcinoma in rats. Ficus glomerata Roxb is an indigenous medicinal plant, belonging to the family Moraceae. It is largely used in herbal and herbo-mineral preparation to treat cancer, cardiovascular diseases, asthma, viral hepatitis and diabetes. DMBA at a dose of 20mg/kg body weight (gastric intubation) significantly elevated the xenobiotic markers such as cytochrome P450 reductase and cytochrome b5 reductase in group (II) rats. On the treatments with the ethanolic extract of Ficus glomerata leaf extract (150 mg/kg bw p.o.) significantly decreased these activities in a group (III) rats when compared to DMBA induced rats, which confirmed its anticancer potential. The TCA cycle marker enzymes namely succinate dehydrogenase, malate dehydrogenase, isocitrate dehydrogenase and NADH dehydrogenase were significantly decreased by DMBA induction in group (II) rats, these enzyme levels were reverted to near normal by the supplementation of F. glomerata in group (III) rats. The results of our present study clearly showed that the F. glomerata possess significant anticancer activity.